Atrioventricular block related to liposomal amphotericin B - Sanches, B (2014)
Atrioventricular block can occur in normal children, young adults or athletes. It is also associated with underlying heart disease or occurs as a drug adverse effect. Amphotericin B is used in the treatment of invasive fungal infections. Cardiac toxicity is a rare adverse reaction. We report the case of a 9-month girl, admitted in the paediatric intensive care unit with cytomegalovirus pneumonitis. During hospitalisation the patient developed a systemic fungic infection and was medicated with liposomal amphotericin B. On the third day of treatment she began repeated episodes of bradycardia with spontaneous reversion. The investigation revealed a second-degree atrioventricular block. We excluded the misplacement of the central catheter, myocarditis or structural cardiomyopathy and suspended amphotericin. After 8 days, the bradycardia episodes ceased what was consistent with the drug's half-life. Amphotericin cardiotoxic mechanism is still unclear. It may be related with alteration of myocardial membrane depolarisation.